Creative Workers: Employment Status and Wage Premiums - Soo Kyeong Hwang (Korea Development Institute (KDI), 2014)
Creative workers-defined here as those with jobs that require creative skills-made up around 12 percent of the total Korean workforce in 2012. While the number of creative workers increased overall between 2008 and 2012, the increase was particularly noticeable among technical creative workers in cultural industries and cultural creative workers in ICT industries. This reflects the growing demand for convergence of cultural creativity and technical creativity. At the same time, an analysis of the wage effect of creative occupations shows that cultural creativity (unlike technical creativity) is systematically undervalued. In order to create new value in creative economy, it is necessary to understand the power of cultural content and stories and encourage their use. - This paper analyzes the characteristics and current situation of the creative economy in Korea, developing definitions for creative occupations and creative workers that are based on creative skills. - The concept of creative workers is defined independently from industry, which makes it appropriate for analyzing the role and results of creative labor throughout the entire economy. - Creative skills are job skills that approach problems from a new or different perspective and contribute to correcting flaws and creating new value. - Cultural creative occupations are defined as jobs that rely on cultural creativity, while technical creative occupations are defined as jobs that rely on technical creativity. - In 2012, there were 2.94 million creative workers in Korea, accounting for 12.2 percent of total employment. This figure grew by around 300,000 in the previous four years. The growth trend was particularly noticeable among cultural creative workers. - Around 30 percent of creative workers, or 900,000, are employed in creative industries. In ICT industries, 68.8 percent of workers in cultural industries and 29.0 percent of workers are creative workers. - The term creativity intensity is defined as the percentage of creative workers in each industry, and can be said to represent that industry's potential for innovation. - Creative intensity continues to increase in cultural industries and ICT industries, but creative intensity in related industries has plateaued at a very low level (6~7 percent). - There was a rapid increase in demand for technical creative workers in cultural industries and for cultural creative workers in ICT industries. - If creative workers are to have the incentive to actually contribute creatively in their work, they must be given appropriate compensation (wages) for this. - There is an income premium for technical creative occupations, yet an income penalty for cultural creative occupations that are not in creative industries. - Cultural creative occupations are generally advantageous to women with regards to wages, but such jobs are less attractive for men. - With attention focused on the convergence between cultural creativity and technical creativity, convergence education must be used in school curriculums to foster mutual understanding. - As long as the demand for creativity remains low in the areas of distribution and consumption, it is unlikely that the virtuous cycle of the creative economy will continue to develop in a way that allows added value to expand through the interaction between production and consumption. - The undervaluation of cultural creativity could become an obstacle to training excellent workers in the cultural industry. - The key to creating a creative ecosystem is respecting spontaneity, discretion, and diversity and providing appropriate incentives for the same.
Keywords: 330